Manajemen e-Government Berbasis Web Model Government-to-Citizen (G2C) Pada Dinas Kebudayaan dan Pariwisata Provinsi Jawa Tengah - Noviana, Rina; Sulandari, Susi; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Information and Communication Technology/IC become very important in the globalization era. At this time begin to grow electronic government (e-gov) as the implementation of information and communication technology using in the Local and Province Government. One of the E-gov applications in the Government Organization, namely regional or provincial government websites. As do with the cultural and tourism agency in Central Java Province implementing government website as the simplest measure to see e-government, its contents still general formation that is needed by the community as the information seekers. The problem is how to manage e-Gov Government-to-Citizen (G2C) model web based in The Culture And Tourism Agency in Central Java Province. This research aim to explain management functions related to e-Gov implementation and to analyze the factors that become an obstacle in the e-Gov management web in The Culture and Tourism Agency in Central Java Province. To answer this problem is by using management function from G.R. Terry. This study used a qualitative exploratory design research. The results of this research showed that e-Gov management based on the web model G2C in The Culture and Tourism Agency in Central Java Province located in the second stages, namely ripening. This condition can be seen from the planning, organizing, actuating and controlling in the culture and tourism Agency in Central Java Province. The management obstacle of e-Gov management based on the web model G2C in The Culture and Tourism Agency in Central Java Province Agency is seen from the process of planning, organizing, actuating, controlling is not yet reached the maximum in overall. Human resources have not been fullest, lack of socialization for the community, sectoral ego in several government local agencies, and lack of budgets from the local governments. There are some improvement and change management in some aspect of planning, organizing, actuating, and controlling. Improving socialization for the community, the existence of a good budget planning, and improving the capabilities of employees is the suggestions to improve.